Core Length: An Alternative Method for Increasing Cancer Detection Rate in Patients with Prostate Cancer - Doluoglu, Omer Gokhan; Yuceturk, Cem Nedim; Eroglu, Muzaffer; Ozgur, Berat Cem; Demirbas, Arif; Karakan, Tolga; Bozkurt, Selen; Resorlu, Berkan (Urology Journal, 2015)
Purpose: We determine whether the lengths of benign and malignant cores affect cancer detection rates in patients with prostate cancer (PCa). Materials and Methods: We evaluated retrospectively 512 patients in our clinic who had undergone 12 core transrectal ultrasound (TRUS)-guided prostate biopsies. The cores were divided into two groups: one with cancer (group 1) and one without cancer (group 2). We also classified Gleason scores as poorly differentiated (scores of 7-10) and moderately differentiated (scores of 5-6); these scores were compared with each other in terms of the core length. The core lengths of the groups were compared using a Student's t-test. A P value of less than .05 was considered to be statistically significant. Results: Of the 512 patients, 76 (15%) had PCa. In total, we evaluated 912 cores of prostate biopsy samples from the 76 patients. Since 92 cores included insufficient tissue and rectal mucosa, we were not able to evaluate them. The remaining 820 cores were divided into two groups. Cancer was detected in 302 cores; 518 cores were benign in nature. The average core length in group 1 was 11.9 ± 4.4 mm, and the average core length in group 2 was 11.1 ± 5.1 mm (P = .015). The core lengths of poorly differentiated and moderately differentiated cancers were similar: 12.3 ± 4.2 mm and 11.7 ± 4.5 mm, respectively (P = .25). Conclusion: Increasing cancer detection rates in cores may be related to core length in TRUS-guided prostate biopsies in PCa patients.